GEJALA FOTOKERATITIS AKUT AKIBAT RADIASI SINAR ULTRAVIOLET (UV) PADA PEKERJA LAS DI PT. PAL INDONESIA SURABAYA - Ananda Kurniawan (Fakultas Kesehatan Masyarakat, Universitas Jember, 2017)
Welding is a job has a high physical risk so that in the process requires considerable skill and specialized equipment. This research was conducted to analyze the UV radiation, workers factors and factors of personal protective equipment that may affect the acute photokeratitis symptoms on welders at the welding workshop Division Kapal Niaga of PT. PAL Indonesia (Persero) Surabaya. This research used a cross-sectional observational analytic method by using a quantitative approach. Observations and interviews were conducted on a sample of 32 workers. The data analysis consisted of univariable and bivariable analysis that used Spearman's test with α = 0.05. The research results show that a significant correlation exists between workers factors ( the age , length of employment , old workings , the distance welding ) with symptoms photokeratitis acute, there were a significant correlation between the use of personal protective equipment (PPE) with symptoms photokeratitis acute, there were a significant correlation between ultraviolet (UV) radiation with acute photokeratitis symptoms and there were no significant correlation between duration of exposure to the acute photokeratitis symptoms. Keywords : the acute photokeratitis symptoms, welder, workers factors, personal protective equipment, ultraviolet radiation